'Only connect': Restoring resilience in the Kalahari ecosystem. (1st November 2019) - Perkins, Jeremy S.
Abstract: As in other semi-arid savannah systems of the world characterised by highly mobile and/or migratory ungulates, Botswana's rangelands are experiencing increased fragmentation due to expanding human activities and increasing human wildlife conflict. Climate change scenarios show Botswana becoming hotter and drier with mega droughts, heat waves and more intense and spatially confined rainfall events. The Botswana Government has reacted by providing artificial water points (AWPs) in the Protected Areas and surrounding Wildlife Management Areas (WMAs), in part to compensate for the lack of access to historical sources due to fences and human expansion. Blanket provision of AWPs will disrupt the existing mobility and migratory strategies of the key ungulates that is basic to their survival and their ability to adapt to climate change. Botswana's burgeoning elephant population has already effectively re-connected the drier Kalahari System to the Northern System by breaching fences in the region. The key recommendations from the past are used to reinforce the need for ecosystem management for resilience at the landscape level via migratory corridors through shared landscapes, made possible by a renewed focus on Community Based Natural Resource Management and Payments for Ecosystem Services. The events that have occurred over the last 50 years are used to illustrate the dangers of managing at the wrong 'localised' spatial and temporal scale and failing to address the key factors of mobility and inequity that characterise the ecological and socio-economic systems, respectively. Highlights: The Kalahari as a major wild animal system is on the verge of collapse. Livestock expansion has blocked mobility between key wet and dry season areas. Adaptation to climate change requires large scale movements (Kalahari–Rift Valley). Community based natural resource management must be re-invigorated. Climate change will exacerbate socio-economic inequities and ecological decline.